Climate and forest plantation: the carbon storage and energy biomass production in Southern Brazil - Schwerz, Felipe (2019)
The search for alternative sources of energy has shown to be a global demand. Motivated by concern about climate change and the depletion of natural resources, the world market has attracted interest in the study and adoption of alternative renewable sources of energy. One possible alternative is the use of forest biomass. In this context, it is necessary to carry out studies that seek to evaluate the growth and yield of different forest species cultivated at different planting spacings. The aim of this study were: (i) to evaluate the production of biomass for energy; (ii) to determine carbon storage and partitioning in the forest system (above-belowground biomass + soil); (iii) to determine the radiation use efficiency of Eucalyptus grandis; and (iv) to characterize the elemental composition and properties of four forest species Eucalyptus grandis, Mimosa scabrella, Ateleia glazioviana, and Acacia mearnsii grown in four planting spacings in Southern Brazil. A field experiment was conducted from September 2008 to September 2018 in the city of Frederico Westphalen, Brazil. The forest biomass was determined by destructive method. Also, the calorific value, elemental composition, immediate chemical analysis, radiation use efficiency, light extinction coefficient, solar radiation interception, leaf area index, biomass yield and partitioning, carbon storage and potential energy yield were evaluated. Information generated in this study is relevant and provides information for companies interested in electricity generation from forest biomass and forest producers thereby assisting in the planning of optimal spacing to be used for biomass production for energy. The highest biomass production, carbon storage, and radiation use efficiency were obtained in the planting spacing (2.0×1.5 m) for the Eucalyptus grandis, which resulted in a higher amount of biomass for energy production. For the other forest species, the optimal planting spacing to produce biomass for energy was the (2.0×1.0 m). Therefore, the use of reduced planting spacing should be prioritized and recommended for future exploitation of forest energy plantations.